Blended learning in English language teaching: A comparison with traditional methods and pedagogical implications - Lekić Jelena; Vešović Marija; Fijuljanin Fahreta (Univerzitetska Misao)
This paper analyzes the implementation of the blended learning approach in English language teaching, comparing it with traditional educational methods. Blended learning, which combines online and traditional face-to-face instruction, offers flexibility, individualization, and the potential for greater student engagement compared to conventional methods. Traditional instruction relies on a frontal approach, where the teacher is the primary source of knowledge, and the student is a passive recipient of information. In contrast, blended learning promotes student autonomy, allowing learners to study at their own pace and utilize technology for personalized learning. Furthermore, the role of the teacher in a blended learning environment shifts from being a knowledge provider to a facilitator, supporting students in the use of digital resources and in developing independent skills. The flexibility of this model enables students to access authentic materials and enhance their language skills through interactive online activities, while face-to-face classes remain focused on more complex interactions and exercises. The conclusion emphasizes the advantages of blended learning in contemporary education, highlighting its potential to enhance the English language learning process through a dynamic and personalized approach.